Female entrepreneurship in rural Vietnam: an exploratory study. Issue 1 (4th March 2014) - Nguyen, Cuc; Frederick, Howard; Nguyen, Huong
Abstract : Purpose: – The purpose of this study was to explore the impact of governmental support policies and socio-cultural influences on female entrepreneurship in rural Vietnam. As such, the study addresses an important literature gap concerning female entrepreneurship within rural communities in South East Asia. Design/methodology/approach: – Qualitative in-depth interviews were conducted with six female entrepreneurs and six female non-entrepreneurs in northern Vietnam to examine the influence of various environmental factors on female entrepreneurship in a rural setting. Findings: – The results suggest that government pro-entrepreneurship policies, together with private sector interventions, have had an impact on rural Vietnam. Yet females in rural and remote Vietnam are still constrained by societal prejudices, financial limitations, and limited entrepreneurship educational opportunities. Originality/value: – The paper's originality lies in its review of the circumstances confronting women in rural Vietnam and its findings concerning the impact of environmental factors on female entrepreneurship in this setting.